DETERMINING THE INFLUENCE OF CHANGES IN THE QUANTITY, SPEED AND COMPOSITION OF VEHICLES AND HIGHWAYS IN THE CITY AND THE DISTRIBUTION OF TRANSPORT - Alisher Kholikov Isan o`g`li; Kasimkhodjaev Bokhodir Kuchkarovich; Ubaydullaev Farkhod Bakhtiyarullaevich (American Journals, 2023)
Developing measures to reduce traffic noise by evaluating and forecasting the traffic-operational state of the city's main streets and ensuring the environmental safety of selected areas along the city's main streets is gaining urgent importance. In recent years, special attention has been paid to the elimination and prevention of existing environmental problems in large cities in our republic. At the same time, the speed of traffic on the main streets of Tashkent city has reached 15,000 vehicles per hour, causing the level of traffic noise in selected areas to exceed the norm by 15-20 dBA.
Keywords: city highway streets, transport, operational condition, transport noise, noise impact, assessment and forecast